Antiproliferative potential of moluccella laevis L. aerial parts family lamiaceae (labiatae), supported by phytochemical investigation and molecular docking study. Issue 5 (4th March 2022) - Hamed, Ashraf N. E.; Abdelaty, Nousiba A.; Attia, Eman Z.; Amin, Mohamed N.; Ali, Taha F. S.; Afifi, Ahmed H.; Abdelmohsen, Usama R.; Desoukey, Samar Y.
Abstract: The current biologically guided study aimed the in vitro investigation of cytotoxic activity, identification of the phytochemical content of Moluccella laevis L. aerial parts and supporting this activity by a molecular docking study. Aqueous fraction demonstrated the most potent cytotoxic effect against CACO-2 with IC50 = 0.067 ± 0.01 μg/mL. Furthermore, EtOAc fraction showed a remarkable cytotoxic activity against MCF-7 cell line with IC50 = 0.35 ± 0.02 μg/mL. Consequently, total ethanolic extract (TEE) and its fractions were subjected to LC-HR-ESI-MS metabolic profiling to discover the constituents that possibly underlie their cytotoxicity. Twenty compounds were tentatively identified from metabolic analysis. Furthermore, eight compounds were isolated. In silico docking study revealed that stachydrine is more likely to account for the antiproliferative activity of both EtOAc and aqueous fractions, probably via its moderate inhibition of receptor tyrosine kinases.